Association between bone mineral density and content and physical growth parameters among children and adolescents diagnosed with HIV: a cross-sectional study - Zanlorenci, Suellem; Martins, Priscila Custódio; Alves Junior, Carlos Alencar Souza; Castro, João Antônio Chula de; Lima, Luiz Rodrigo Augustemak de; Edio Luiz Petroski; Silva, Diego Augusto Santos (São Paulo Medical Journal, 2022)
BACKGROUND: During childhood and adolescence, there are significant increases in bone mineral content (BMC) and bone mineral density (BMD). OBJECTIVE: To investigate physical growth parameters associated with BMD and BMC among children and adolescents diagnosed with human immunodeficiency virus (HIV). DESIGN AND SETTING: Cross-sectional study conducted in Florianópolis, Brazil, among 63 children and adolescents (aged 8-15 years) diagnosed with HIV. METHOD: BMD, BMC and fat percentage z score were evaluated using dual X-ray absorptiometry. Age/height z score and body mass index (BMI)/age z score were obtained in accordance with international recommendations, and bone age was obtained through hand-wrist radiography. Sex, family income, information on HIV infection (T CD4+ lymphocyte count, viral load and type of antiretroviral therapy, moderate-vigorous physical activity and sedentary behavior) were used as adjustment variables in the analyses. Simple and multiple linear regression analyses were performed, with a significance level of P ≤ 0.05. RESULTS: Subtotal BMD (without the head region) was directly associated with bone age, BMI/age z score and fat percentage z score, even after adjusting for covariates. Subtotal BMC/height was directly associated with bone age, height/age z score, BMI/age z score and fat percentage z score, even after adjusting for covariates. CONCLUSION: Subtotal BMD and subtotal BMC/height were directly associated with physical growth indicators among children and adolescents diagnosed with HIV.